2016
DOI: 10.1080/10826084.2016.1245333
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Social Networks and Alcohol Use: Variability by Gender and Type

Abstract: Background Scientists have established that social networks influence adolescents’ substance use behavior, an influence that varies by gender. However, the role of gender in this mechanism of influence remains poorly understood. Particularly, the role an adolescent’s gender, alongside the gender composition of his/her network, plays in facilitating or constraining alcohol use is still unclear. Objectives This study examined the associations among the gender composition of adolescents’ networks, select networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Findings from this study align with prior work that found alcohol and tobacco consumption are related to increased social comparison scale scores 12 . Our results reinforce that high school girls' social relationships play a role in shaping their own alcohol use, 37 and illicit drug use behaviors 38 . Early adolescent normative perceptions among peers have also been related to heavy alcohol use during the high school years 39,40 …”
Section: Discussionsupporting
confidence: 88%
“…Findings from this study align with prior work that found alcohol and tobacco consumption are related to increased social comparison scale scores 12 . Our results reinforce that high school girls' social relationships play a role in shaping their own alcohol use, 37 and illicit drug use behaviors 38 . Early adolescent normative perceptions among peers have also been related to heavy alcohol use during the high school years 39,40 …”
Section: Discussionsupporting
confidence: 88%
“…Often the constraints on scheduled days are thought of in terms of structural demands, such as school or work start times [25,65], but in adolescence, increased academic and social engagement as well as lifestyle choices are likely to contribute to increased social jetlag [27]. Given that alcohol use is most often a social behavior [66,67] and is well documented to be influenced by peer behavior [68][69][70][71], it is possible that alcohol use in this study reflects a social influence on sleep behavior. Further research on possible social influences (e.g., changes in parental monitoring and peer norms and activities) on the alcohol-sleep relations is merited.…”
Section: Cross-lagged Associationsmentioning
confidence: 97%
“…More in detail, the role an adolescent’s gender, alongside the gender composition of his/her network, plays in teenager approach to alcohol use is far to be fully understood. A study reported in Jacobs et al ( 2017 ) investigated the associations among the gender composition of adolescents’ networks, select network characteristics, intra-personal, inter-personal factors and alcohol use for a sample of US adolescents. The authors performed cross-sectional data from a 2010 study of 1,523 high school students from a school district in Los Angeles.…”
Section: Analyzing Sn Variabilitymentioning
confidence: 99%